2022
DOI: 10.17221/94/2021-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Association of rumination with milk yield of early, mid and late lactation dairy cows

Abstract: Identification of the associations of cow feeding behaviour with milk yield (MY) is important for supporting recommendations of strategies that optimize MY. The objective of this study was to identify associations between measures of rumination time (RT) and MY using data collated from 2 777 dairy cows on nine commercial dairy farms during the years 2017 to 2019. A database contained behaviour and daily MY data. Cows averaged (mean ± standard deviation) 2.7 ± 1.6 lactations, 153 ± 81 days in milk, and 23.2 ± 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Johnston and DeVries (2018) also found a correlation between the milk yield, eating time and rumination time of dairy cows. High-yielding cows tend to have greater feed intake to support energy demand (Krpalkova et al 2022). Our results of linear regression confirmed that milk production is positively influenced by feed intake (Shabi et al 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Johnston and DeVries (2018) also found a correlation between the milk yield, eating time and rumination time of dairy cows. High-yielding cows tend to have greater feed intake to support energy demand (Krpalkova et al 2022). Our results of linear regression confirmed that milk production is positively influenced by feed intake (Shabi et al 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Identifying the association of cow feeding behaviour with MY is important to support the recommendation of strategies that optimize MY (Krpalkova et al 2022). The behavioural differences observed in this study provide new insights into the effects of RT and FT on MY.…”
Section: Milk Performance Parametersmentioning
confidence: 80%
“…Data obtained by sensors were compared with the observations by Krpalkova et al (2022). The aim of their study was to identify associations between RT and MY measurements using data collected from 2 777 dairy cows on nine commercial dairy farms in several European countries between 2017 and 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows with longer rumination times show a higher rumen protozoa count and activity [ 54 ]. In turn, a longer rumination time also translates into a higher milk yield [ 55 ]. Cows in the HCS group were at a higher risk of a negative energy balance and metabolic disease, indicated by a higher milk yield supported by a higher rumination time.…”
Section: Discussionmentioning
confidence: 99%